Complexation of Titana‐ and Zirconadihydrofuran Metallacycles with Organoaluminium Compounds and Catalytic Activity of the Resulting Complexes in Polymerization of ϵ‐Caprolactone. Issue 1 (11th January 2017) - Burlakov, Vladimir V.; Bogdanov, Vyacheslav S.; Sokolova, Olga O.; Arndt, Perdita; Spannenberg, Anke; Kh. Minacheva, Mariya; Lyssenko, Konstantin A.; Anan'ev, Iwan A.; Rosenthal, Uwe; Shur, Vladimir B.
Abstract: The interaction of the titanadihydrofuran metallacycles Cp2 Ti[η 2 ‐C(SiMe3 )=C(Ph)‐C(Me)2 O] (1 ) and Cp2 Ti[η 2 ‐C(SiMe3 )= C(Ph)‐CH(Ph)O] (2 ) with i Bu2 AlH in n ‐hexane at 20°C yields 1 : 1 complexes Cp2 Ti[η 2 ‐C(SiMe3 )=C(Ph)‐C(Me)2 O]( i Bu2 AlH) (4 ) and Cp2 Ti[η 2 ‐C(SiMe3 )=C(Ph)‐CH(Ph)O]( i Bu2 AlH) (5 ) respectively. According to X‐ray diffraction data, the i Bu2 AlH molecule in4 is coordinated by its aluminium centre with the oxygen atom whereas the hydride hydrogen atom of the i Bu2 AlH forms a bridge with the titanium. As a result of the complexation with i Bu2 AlH, the Ti−O and Ti‐C(SiMe3 ) bonds of the starting1 are strongly elongated. An analogous 1 : 1 adduct (11 ) is formed in the interaction of i Bu2 AlH with the zirconadihydrofuran derivative Cp2 Zr[η 2 ‐C(SiMe3 )=C(SiMe3 )‐C(Me)2 O] (3 ). Like the Ti−O and Ti‐C(SiMe3 ) bonds in1, the Zr−O and Zr‐C(SiMe3 ) bonds in3 are considerably elongated as a result of the coordination with i Bu2 AlH. The reaction of1 with EtAlCl2 gives a complex, Cp2 Ti[η 2 ‐C(SiMe3 )=C(Ph)‐C(Me)2 O](EtAlCl2 ) (8 ), in which the organoaluminium compound is also coordinated by its aluminium centre with the oxygen atom. This leads to a strong elongation of the Ti−O bond. The C−O bond of the metallacycle in8 is noticeably elongated as well but the Ti‐C(SiMe3 ) bond length even somewhat shortens. Complexes4, 5, 8 and11 are capable of catalysing ring‐opening polymerization of ϵ‐caprolactone. The highest activity is exhibited by complexes4 and5 . Abstract : The interaction of metalladihydrofurans Cp2 Ti[ η 2 ‐C(SiMe3 )=C(Ph)‐CR 1 (R 2 )O] (R 1 =R 2 =Me (1 ); R 1 =H, R 2 =Ph) and Cp2 Zr[ η 2 ‐C(SiMe3 )=C(SiMe3 )‐C(Me)2 O] with i Bu2 AlH gives 1:1 complexes containing the Al−H−M bridge (M=Ti, Zr) along with the coordination Al−O bond. By contrast, the reaction of1 with EtAlCl2 yields a 1:1 adduct containing only the coordination Al−O unit. All the complexes obtained are capable of catalysing the ring‐opening polymerization of ϵ‐caprolactone.